"I can't cope seeing my kids … hearing these kinds of prayers." Parents' rationale for choosing state-funded Muslim schools in the Republic of Ireland: an ethnographic study. Issue 3 (2nd September 2018) - Sai, Youcef
ABSTRACT: The population of Muslims living in the Republic of Ireland has increased significantly in recent years. Despite Muslims being one of the fastest growing minorities in the country, there is a paucity of research on the educational choices of Muslim parents. This study draws on ethnographic fieldwork conducted between 2013 and 2014. Based on semi-structured interviews, this article focuses on the views of Muslim parents and teachers from two Muslim state-funded primary schools in Ireland. The interviews revealed that, for most parents, the schools' Islamic ethos was an underlying motivation for enrolling their children at Muslim schools. The findings also demonstrate the negative reasons of their choices, such as the lack of accommodation and the feelings of isolation they and their children experienced in non-Muslim schools, which further heightens the perception that Muslim schools in Ireland act as safe environments that protect the cultural and religious identities of Muslim children. The article concludes with some considerations for future research.